Working toward a transdisciplinary approach to teaching and learning planetary health–A collective reflection - Dambre, Cato; Strack Diaz, Julia Gabriela; Orhan, Rana; Montag, Doreen; van der Zande, Indira; Gallo, Valentina (Frontiers in Public Health, 2022)
Background In order to educate the next generation of leaders to work at reverting the damaging effects of the Anthropocene, there is an increasing need to incorporate more environmental-related aspects in all teaching programmes, including the health-related. Planetary health is a complex field which can benefit from a transdisciplinary pedagogical approach. The aim of this research was to evaluate an approach working toward transdisciplinarity applied to a course of Planetary Health taught at the Bachelor degree Global Responsibility & Leadership of the University of Groningen through substantive feedback and reflections from the students. Methods By the end of the course, a focus group was conducted with the students inviting them to reflect on the different aspects of the pedagogical approach, evaluating their effectiveness. A thematic analysis was conducted on the transcribed focus group. Results The students appreciated the added value of working toward a transdisciplinary approach and peer-to-peer learning and teaching adopted in the Planetary Health course, as a way of enhancing their learning experience. They pointed out the need of incorporating a transcultural approach into the transdisciplinary one, as a way not only to improve their learning experience, but also to enrich the transdisciplinarity itself. Conclusion Incorporating a process toward transdisciplinary and transcultural teaching of planetary health into undergraduate programmes was found to be of added value. The peer-to-peer horizontal learning opportunities were seen as a way for taking advantage of the collaborative, informal teaching and community building serving the overall scope of the course.